Credit unions' acquisitions of banks and thrifts. Issue 3 (5th August 2019) - Walker, David A.; Smith, Kathryn I.
Abstract : Purpose: In total, 14 credit unions have acquired 16 banks and savings institutions since 2012; 7 additional acquisitions are in progress and are expected to close before year-end 2019. The analysis of the population of these acquisitions spans the paths of annual differences in CAMEL ratios. Most acquirers have a somewhat revised capital structure and are often benefiting from economies of scope, as well as economies of scale. Since their acquisitions, the acquiring credit unions have become less risky, measured by simulated CAMEL ratios, and they are lending a larger share of their deposits. There is no apparent financial reason to discourage credit unions from acquiring additional banks and savings institutions. The National Credit Union Administration does not need to be particularly hesitant to allow credit unions to acquire banks and thrifts. Design/methodology/approach: Financial analysis is done via simulated CAMEL ratios. Findings: After acquiring banks, credit unions are less risky and lend a greater share of their deposits. Research limitations/implications: The study analyzes the population of the credit unions that have acquired banks since 2012, but the population consists of 14 banks acquiring 16 credit unions. Practical implications: Credit unions should not be prohibited from further acquisitions of banks and thrifts. Social implications: Credit union members are better served after a credit union acquires a bank. Originality/value: No previous study has explored the effects of credit unions acquiring banks and thrifts, which began in 2012.